Banks and Securities Markets: Corporate Financing in Germany and the UK. - Alexander, I; Mayer, C (CEPR, 1990)
This paper compares corporate financing in the German bank-based and UK market-based systems. Large German firms pay out a lower proportion of their profits as dividends and finance a larger proportion of their investments from retentions. German banks extend more long-term finance to medium-sized firms but UK firms raise more new equity. The paper tests alternative theories of corporate finance. It finds no relation between finance and taxation, and information theories only receive limited support. Instead, it concludes that control models of corporate finance are consistent with observed patterns of finan.